Lactic acid bacteria : biodiversity and taxonomy - Holzapfel, W. H.; Wood, Brian J. B. (Chichester, UK : Wiley Blackwell, 2014)
'This book provides a much-needed and comprehensive account of the current knowledge of the lactic acid bacteria, covering the taxonomy, biochemistry, physiology and molecular biology of these scientifically and commercially important micro-organisms'--
'The lactic acid bacteria (LAB) are a group of related micro-organisms that are enormously important in the food and beverage industries, preventing food spoilage and extending shelf life. This is the first reference that provides a much-needed and comprehensive account of the current knowledge of LAB, detailing the taxonomy, biochemistry, physiology, and molecular biology of these scientifically and commercially important micro-organisms. With chapter coverage of every recognized genus and species, this book will enable researchers to fully exploit the industrial, nutritional, and medical applications of these organisms'--
Section I. Introduction: The Lactic Acid Bacteria in present day context -- Introduction to the LAB -- Physiology of the LAB -- Phylogenetics and Systematics -- Overview on the ecology and biodiversity of the lactic acid bacteria -- Comparative genomics of Lactobacillus and other lactic acid bacteria -- Section II. Family Aerococcaceae -- The genus Abiotrophia -- Aerococcus -- The genus Facklamia -- Minor genera of the Aerococcaceae (Dolosicoccus, Eremococcus, Globicatella, Ignavigranum) -- Section III. Family Carnobacteriaceae -- The genus Carnobacterium -- The Genus Marinilactibacillus -- The genus Trichococcus -- The genus Alkalibacterium -- Minor Genera of Carnobacteriaceae : Allofustis, Alloiococcus, Atopobacter, Atopococcus, Atopostipes, Bavariicoccus, Desemzia, Dolosigranulum, Granulicatella, Isobaculum and Lacticigenium -- Section IV: The family Enterococcaceae -- Genus Enterococcus -- Genus Tetragenococcus -- Genus Vagococcus -- Minor genera in Enterococcaceae : Catellicoccus, Melissococcus and Pilibacter -- Section V. Family Lactobacillaceae -- The genus Lactobacillus -- The genus Paralactobacillus -- The genus Pediococcus -- The genus Fructobacillus -- Section V. Family Leuconostocaceae -- The genus Leuconostoc -- The genus Oenococcus -- The genus Weissella -- Section VII. The family Streptococcaceae -- Genus Lactococcus -- Genus Lactovum -- The genus Streptococcus -- Section VIII. Physiologically'related' Genera -- Genus Bifidobacterium with notes on the genera Scardovia and Parascardovia -- Genus Sporolactobacillus -- Genera Bacillus, Geobacillus, and Halobacillus -- The Genera Halolactibacillus and Paraliobacillus.
Includes bibliographical references and index.
Keywords: Lactic acid bacteria; Biodiversity; Microbial diversity; Lactic acid bacteria -- Classification; Lactic acid bacteria -- Physiology; Microbiological chemistry; Lactic acid bacteria -- Molecular aspects